Resumption of Autophagy by Ubisol-Q10 in Presenilin-1 Mutated Fibroblasts and Transgenic AD Mice: Implications for Inhibition of Senescence and Neuroprotection. (24th December 2019) - Vegh, Caleb; Pupulin, Simon; Wear, Darcy; Culmone, Lauren; Huggard, Rachel; Ma, Dennis; Pandey, Siyaram
Abstract : Alzheimer's disease (AD) is the most prevalent form of dementia and is associated with loss of memory, amyloid-beta plaque buildup, and neurofibrillary tangles. These features might be a result of neuronal cell death in the cerebral cortex and hippocampal regions of the brain. AD pathologies can be attributed to a variety of biochemical consequences including mitochondrial dysfunction, increased oxidative stress, and autophagy inhibition. Unfortunately, current therapeutics are limited only to symptomatic relief and do not halt the progression of neurodegeneration. Previous in vitro experiments have shown that a water-soluble formulation of coenzyme-Q10, Ubisol-Q10, can stabilize the mitochondria, prevent oxidative stress, and inhibit premature senescence in fibroblasts of AD patients. Since autophagy plays a critical role in maintenance and survival of neurons, we hypothesized that Ubisol-Q10 treatment could result in resumption of autophagy. Indeed, we observed induction of autophagy by Ubisol-Q10 treatment in AD fibroblasts as well as in the brains of transgenic AD mice. We found increased expression of autophagy-related genes beclin-1 and JNK1 following Ubisol-Q10 treatment of AD fibroblasts. These results were confirmed at the protein level by immunofluorescence and Western blotting. Interestingly, despite reduction of oxidative stress in cells due to Ubisol-Q10 treatment, autophagy inhibition leads to resumption of premature senescence in these PS-1 mutated fibroblasts indicating that autophagy is critical to prevent the senescence phenotype. Withdrawal of Ubisol-Q10 treatment also leads to the return of the senescence phenotype in AD fibroblasts indicating that constant supplementation of Ubisol-Q10 is required. Additionally, Ubisol-Q10 supplementation in the drinking water of double transgenic AD mice leads to increased expression of beclin-1 and JNK1 in the cortical region. Thus, the activation of autophagy by Ubisol-Q10 could be the mechanism for its ability to halt the progression of AD pathology in transgenic AD mice shown previously.